New exact solutions of the Tzitzéica-type equations in non-linear optics using the expa function method. Issue 7 (16th April 2018) - Hosseini, K.; Ayati, Z.; Ansari, R.
Abstract: One specific class of non-linear evolution equations, known as the Tzitzéica-type equations, has received great attention from a group of researchers involved in non-linear science. In this article, new exact solutions of the Tzitzéica-type equations arising in non-linear optics, including the Tzitzéica, Dodd–Bullough–Mikhailov and Tzitzéica–Dodd–Bullough equations, are obtained using the exp a function method. The integration technique actually suggests a useful and reliable method to extract new exact solutions of a wide range of non-linear evolution equations.